2004
DOI: 10.1097/00129492-200403000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Ossicular Reconstruction Using Bone Cement

Abstract: The use of POPs and incus interposition grafts is fraught with the possibility of migration and resultant recurrent conductive hearing loss. Using bone cement to reconstruct the ossicular chain restores the integrity of the ossicular chain in the most natural of ways. This reconstruction technique provides an excellent alternative to currently accepted methods and should be considered for incus-stapes disarticulation. There has been no dissolution of the bone source and the results have persisted thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 12 publications
3
67
0
5
Order By: Relevance
“…(+)-Tartaric acid (5-10 wt.%) ( Figure 5A) improves the rheological properties of GPCs by extending the working time and sharpening the onset of the setting time [40]. Results of Wilson et al were confirmed by Prosser et al [87], who showed by means of 13 C Fourier transform NMR spectroscopy that tartaric acid reacts preferentially with the glass and prevents the early binding of cations to the polyanion chains, resulting in increased working time. Tartaric acid is fully complexed at pH≈3, and complexing by PAA then occurs with the pH of the set cement rising to pH≈5 [87].…”
Section: Effect Of Additives/chelating Agentsmentioning
confidence: 83%
See 1 more Smart Citation
“…(+)-Tartaric acid (5-10 wt.%) ( Figure 5A) improves the rheological properties of GPCs by extending the working time and sharpening the onset of the setting time [40]. Results of Wilson et al were confirmed by Prosser et al [87], who showed by means of 13 C Fourier transform NMR spectroscopy that tartaric acid reacts preferentially with the glass and prevents the early binding of cations to the polyanion chains, resulting in increased working time. Tartaric acid is fully complexed at pH≈3, and complexing by PAA then occurs with the pH of the set cement rising to pH≈5 [87].…”
Section: Effect Of Additives/chelating Agentsmentioning
confidence: 83%
“…These features have made them attractive candidates for expanded applications in hard tissue repair. However, whilst their use in orthopedic applications has long been mooted, their non-dental clinical use has been limited to ear, nose and throat applications [10][11][12][13]. This is due to certain outages in their properties, including the following [2,14]: (a) Clinical literature supporting defective osteoneogenesis and fatal encephalopathy arising from aluminum ions (Al The majority of research into CGPCs has focused on changing the glass composition because it is capable of controlling both setting chemistry, strength [15,16] and ion release.…”
Section: Introductionmentioning
confidence: 99%
“…Following hardening, the movement of the ossicles is checked. An exothermic reaction appears after the application of GIC [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…These techniques can now be replaced by ossicular bridging with hydroxyapatite bone cement. Biocements have proved their value in otologic surgery as they have ideal adhesive and osseointegrative characteristics [10] . A major advantage is the fact that the ossicular chain can be restored in a more physiologic way and with only minimal manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…While biocompatible prostheses were initially developed to improve hearing in chronic middle ear disease and otosclerosis, they also proved their usefulness in traumatic disease treatment [2][3][4][5][6][7][8][9] . A recent innovation is the application of hydroxyapatite bone cement, which appears to be a reliable technique to restore the energy transfer in a more physiological way [10,11] . Ossicular dislocations are far more common than fractures.…”
Section: Introductionmentioning
confidence: 99%